Self-reported weight changes in 1st year university students in England: an analysis of social and physical environment - Vadeboncoeur, C (2016)
Background: Moving from secondary education to university is an important transitional moment during which students commonly experience a weight change (WC). This WC in first year university students (FYUS) is described as the Freshmen 15, in reference to claims that students gain 15lbs (6.8kg) over the academic year. Past research suggest the WC is closer to an average of 2kg and is due to physical inactivity, stress and poor diet. The socio-ecological model (SEM) offers a conceptual framework, reflecting many levels of influence to describe health behaviours in specific settings and is relevant to this context. My thesis sought to understand self-reported WC in FYUS in England adopting an SEM perspective. Methods: I conducted a literature review to evaluate the strength and quality of observational evidence to support the hypothesis of the Freshmen 15. With data from 32 identified studies, I performed a meta-analysis on mean WC. I also performed sub-analyses stratified by sex, location, weight measuring method and by weight gainers. Based on the results and identified knowledge gaps, I then developed a national study on FYUS self-reported weight change in England through an online survey and collection of national statistics. I recruited FYUS from 28 universities, from a total of 101 universities. Students answered an online survey at three time points over the 2014-2015 academic year. They reported their weight, height and answered questions representing 29 constructs at the demographics, intrapersonal, interpersonal and environmental level, reflecting the SEM. I performed descriptive statistics and stepwise AIC regressions to examine WC trends and to explore which variables explain WC. Analyses were conducted on the full sample over the academic year, by term, sex and weight gaining status. Results: The meta-analysis and literature review indicated that 60% of FYUS gained weight with an average gain of 3.38kg over 7-8 months. For my empirical study, I recruited 1,026 students, of which 215 were eligible and answered the survey at all three time points. The mean self-reported WC was +0.98kg, 50% gained weight at an average of 3.46kg while 25% lost weight at an average of 3.21kg. The best AIC model indicated that correlates from all layers of the SEM were useful in describing WC over the academic year, with an adjusted-R2 of 25.3%. Across all multivariate models, explanatory variables for self-reported WC included the undergraduate/postgraduate ratio of a university, being part of healthy universities network, perceived quantity of green space, unhealthy eating with friends and baseline weight. Conclusion: The results indicate that 75% of FYUS experience WC at an average of +/- 3.2kg, equivalent to a Freshmen 7. The multivariate models support the use of an SEM approach in investigating first year university WC and in developing healthy environments. Universities should embrace their potential for health promotion as their social and physical environments influence WC.